Pengaruh Sistem Pengendalian Internal dan Komitmen Organisasi Terhadap Kecenderungan Kecurangan Akuntansi: Studi Empiris pada Koperasi Serba Usaha se-Kecamatan Gianyar - Luh Yunadi Marsela; Indraswarawati, Sang Ayu Putu Arie; Satriya , I Wayan Budi (UNHI Press, 2025)
T The skill or desire of an individual to handle or utilize their own financial information in a way that ultimately hurts other people is known as accounting fraud. This study sought to determine how organizational committees and internal control systems affected accounting in Gianyar Province businesses. Purposive and non-probabilistic selection methods were used to choose 160 respondents from among 51 operating firms in Gianyar Province for this study. Multiple linear regression analysis was used to examine the collected data. The results of the study demonstrated that local accounting fraud was significantly impacted negatively by the internal control system. Moreover, the local community suffers greatly as a result of organizational deception. This suggests that a firm is more resilient and that the likelihood of accounting fraud is reduced the better the internal control system is put in place.